2013
DOI: 10.2119/molmed.2013.00081
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Antibacterial Effects of Cystatin 9 against Francisella tularensis

Abstract: Cystatin 9 (CST9) is a member of the type 2 cysteine protease inhibitor family, which has been shown to have immunomodulatory effects that restrain inflammation, but its functions against bacterial infections are unknown. Here, we report that purified human recombinant (r)CST9 protects against the deadly bacterium Francisella tularensis (Ft) in vitro and in vivo. Macrophages infected with the Ft human pathogen Schu 4 (S4), then given 50 pg of rCST9 exhibited significantly decreased intracellular bacterial repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…We were the first investigative team to report that a single i.n. dose of rCST9 (50 pg) attenuated the pathophysiological effects of the deadly human pathogen F. tularensis , resulting in clearance of the pulmonary infection and leading to remarkable improvements in survival rates ( 15 ). The success of these studies led us to examine the protective effects of rCST9 in an experimental mouse model of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We were the first investigative team to report that a single i.n. dose of rCST9 (50 pg) attenuated the pathophysiological effects of the deadly human pathogen F. tularensis , resulting in clearance of the pulmonary infection and leading to remarkable improvements in survival rates ( 15 ). The success of these studies led us to examine the protective effects of rCST9 in an experimental mouse model of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we previously reported that rCST9 directly decreased the viability and virulence of the deadly human pathogen F. tularensis Schu 4. Proteomic analysis of F. tularensis exposed to rCST9 showed that the cysteine proteinase inhibitor markedly diminished or eliminated key metabolic proteins in the pathogen, thereby preventing nutritional processing and energy production ( 15 ). rCST9 also interfered with the cell wall synthesis of F. tularensis ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations